Pacific century : - Borthwick, Mark (Westview Press, 1998)
The Asia-Pacific region now looks set to become a major economic and political global force. Focusing on both southeast and northeast Asia, this highly illustrated volume examines the broad, cross-cutting themes of regional history, emphasizing the interactions between cultures and nations. Spanning the whole history of the Pacific Asia, from ancient times to the present day, the book concludes with a look at the probable future for the nations of this rapidly emerging region. Poised to enter the twenty-first century, the Asia-Pacific region is rapidly emerging as a global economic and political powerhouse. This illustrated volume stresses broad, cross-cutting themes of regional history with an emphasis on the interactions between cultures and nations. The author begins with an overview of political evolution and cultural and economic trends since ancient times and then considers more recent developments in their historical context, noting that prior to the current economic boom there were at least two great ages of commerce in the Pacific Basin. The conclusion weighs the key domestic and international issues facing the nations of Pacific Asia and evaluates the interactions of these countries with North America and with the global economy.